Algoritmo para predição de risco de epidemia de phakopsora pachyrhizi em soja - Lerner, Maíne Alessandra (2016)
The control of asian soybean rust depends on the application of fungicides at the right time. The use of forecasting systems is an important tool in the decision-making process. This work aims to estimate a prediction algorithm that generates risk levels of Phakopsora pachyrhizi infection based on rainfall, minimum temperature, sowing date, growth stage of the crop and local, aimed at applying fungicides products at the correct time. Four experiments were conducted in the experimental area of Phytus Institute, Itaara city, central region of Rio Grande do Sul, in the crop 2014/2015. Each experiment corresponded to a different sowing date and consisted of treatments: control (T1) without fungicide application; application as recommended in the algorithm to be assessed (T2), application of the scheduled program in days after emergence (DAE) (T3), based on growth stage of the crop (T4), application as recommended in the algorithm with seven days delay (T5), application of the scheduled program in days after emergence with seven days delay (T6) and application based on growth stage of the crop with seven days delay (T7). To evaluate the effect of treatments were determined to AUCPD, rate of progress, productivity, weight of a thousand grains, and correlations between the dependent and independent variables related to the first pustule and disease severity. The positioning defined by the use of the algorithm did not provide superiority over AUCPD variable rate of progress, productivity and weight of a thousand grains, compared to other treatments in none of the experiments. Asian rust occurred at different growth stages of soybean and the use of sowing dates may indirectly measure the pressure of inoculum of this pathogen. The seven-day period is not consistent for the calculation of the meteorological variables that precede the disease. Temperature was not relevant to explain the epidemic and its use in the algorithm not justified. Rainfall had decisive influence on the epidemic and the more periods of rain occurred, the higher were the severity levels.